EFEKTIFITAS PEMBELAJARAN GOOGLE CLASSROOM PADA MAHASISWA JURUSAN ILMU KOMUNIKASI DI ERA PANDEMI COVID-19 - Ayu Melda Rina; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The google classroom application plays a very important role in the learning process in the era of the Covid-19 pandemic, especially for students. The purpose of this study was to determine how effective Google Classroom learning was for students majoring in communication science in the era of the covid-19 pandemic. The method used is descriptive quantitative, the population of the 2015-2020 class of communication science majors is 700. 10% is taken using the Slovin formula, a sample of 88 people is obtained with a positive sampling technique, the data collection technique used is questionnaires and documentation and tested using SPSS 23. The results showed that the effectiveness of Goggle Classroom learning for Communication Science students in the Covid-19 pandemic era was seen from the average convenience indicator of 3.21 and classified as effective, then the benefit indicator was 2.97 classified as effective and the quality indicator was 3. ,14 is considered effective. Overall, the effectiveness of Goggle Classroom learning for Communication Studies students in the Covid-19 pandemic era is considered effective. Keywords: Effectiveness, Google Classroom, Pandemic  Covid-19